Effect of Spent Button Mushroom Substrate on Yield and Quality of Baby Spinach (Spinacia oleracea) - Forbes B. Muchena; Charity Pisa; Moses Mutetwa; Chido Govera; Wonder Ngezimana (International Journal of Agronomy)
Disposal of spent mushroom substrate (SMS) generated after mushroom cultivation is a subject of great concern. Unplanned disposal causes land, water, and air pollution together with the nuisance in the surroundings. During recent years, environmental legislation has forced mushroom growers to think about more amicable ways of SMS disposal. Hence, farmers in different corners of the country are using SMS as manure for various field crops and horticulture but without any support of the recommended rates from scientific data and therefore may not be getting the optimum benefits. This study sought to evaluate the effects of spent mushroom substrate on the yield and quality of baby spinach. The experiment was conducted in Mazowe, Zimbabwe, with 5 treatments (10 t ha−1, 20 t ha−1, 30 t ha−1 of SMS, and two controls) arranged in a CRBD and replicated 3 times. Biomass production (fresh mass, dry mass, root length, fresh root mass, and dry root mass) and sensory evaluation were determined 35 days after planting. Results showed that increasing rates of spent mushroom substrate significantly (p < 0.05) increased the fresh yield and quality of baby spinach. Application of spent mushroom substrate beyond 30 t ha−1, however, increased the bitterness of baby spinach. The results of the study present the potential of the spent mushroom substrate as an organic fertilizer for the production of quality baby spinach.